Estimation of Resistin and Immunoglobulins (IgA and IgM) Levels in the Serum of Iraqi Patients with Type 1 and Type 2 DiabetesMellitus - Saihood, Yahya Dreaim; Abbas, Ali Hafedh; Hassan, Ibtesam Badday (Iraqi Journal of Science, 2024)
Resistin (RE) is a cysteine rich polypeptide. It has been established that in humans adipocytes, pancreatic cells, muscle, and mononuclear cells all express this 108 amino acid polypeptide. It is important to note that resistin is primarily produced by peripheral blood mononuclear cells (PBMCs) in humans. Its part in the inflammatory processes has been proven. Immunoglobulins IgA and IgM are crucial elements of humoralimmunity. They increase inflammatory responses and the removal of immunological complexes by activating the complement system, sensitizing natural killer cells, phagocytes, and mast cells, and regulating cytotoxic cellular activity. The aim of this study was to determine resistin and immunoglobulin IgA and IgM levels in the serum of type 1 diabetic (T1DM) and type 2 diabetic (T2DM) patients and the healthy control. This respective study was carried out at the National Center for Diabetes Treatment and Research and the consulting clinics in Al-Muqdadiya District and Baquba District in Iraq during the period from January 2022 to April 2022. It included 153 participants; divided into 3 groups (51 patients with T1DM and 52 patients with T2DM, and 50 healthy control). The result of serum resistin showed that there was a highly significant difference when comparing the mean of serum resistin of T1DM with that of T2DM patients group and the control group. While no significant difference was detected when the mean of serum resistin ofthe T2DM patients group with that of the control group was compared. The mean of immunoglobulins IgA and IgM were compared in T1DM , T2DM patients and the healthy controls with significant differences between the three groups. It can, therefore, be concluded that increased serum resistin levels were recorded in T1DM patients than T2DM patients and healthy control. Increased serum immunoglobulins IgA and IgM levels were also noticed in T1DM and T2DM patients compared with control.